PENGARUH LABA BERSIH, ARUS KAS DAN LIKUIDITAS TERHADAP HARGA SAHAM (Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2018 – 2022) - Tilam Sari, Titis; Fauziah, Diah (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This research aims to determine partially and simultaneously the influence of net profit, cash flow and current ratio on stock prices. This research uses secondary data sourced from the annual financial reports of pharmaceutical companies listed on the IDX during the 2018-2022 period. Sample selection used purposive sampling method. The analytical method used is multiple linear regression analysis by first carrying out classical assumption tests, normality, multicollinearity, heteroscedasticity, autocorrelation, correlation, coefficient of determination, t test and F test which are processed using SPSS 23 software. Based on data analysis. Partially, the independent variables that have a significant positive influence on share prices are net profit with a t-count value of 2.131 > t-table 1.705 and a sig value of 0.043 < 0.05 and net cash flow with a t-count value of 2.134 > t-table 1.705 and the sig value is 0.042 <0.05. Meanwhile, the independent variable that has a significant negative influence on share prices is the current ratio with a t-count value of –3.807 < t-table 1.705 and a sig value of 0.001 < 0.005. In terms of net profit, cash flow and current ratio, they simultaneously influence stock prices with an F-count value of 8.242 > F-table 2.96 and a sig value of 0.001 < 0.05.